2013
DOI: 10.1089/aid.2012.0107
|View full text |Cite
|
Sign up to set email alerts
|

Distribution OfCCR-5Δ32,CCR2-64I, andSDF-1-3′AAlleles Among Jordanians

Abstract: Entry of HIV virus into cells is mediated by chemokine receptors. Genetic variations in chemokine receptors have been shown to modulate susceptibility to HIV infection and disease course. In this study, the frequencies of CCR5 (CCR5-Δ32), CCR2 (CCR2-64I), and SDF-1 (SDF-1-3') gene polymorphisms were determined in a Jordanian population. A total of 540 subjects were randomly selected from different regions of Jordan (South, Middle, and North). Six individuals were found to carry the CCR5-Δ32 allele (0.6%) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…In Portugal, one of the countries that has most significantly influenced the genetic background of the Brazilian population, a frequency of 8% was reported for the general population, which is at the limit of statistical significance when compared with the frequency observed in this study (P = 0.05) (Carvalho et al, 2014). In Middle Eastern countries, variation in the allele-D32 frequency was more apparent, ranging from 0.6-14%, with the highest frequencies found in Turkey (9.1%) and Israel (14.3 %) (P < 0.05) (Martinson et al, 2000;Khabour et al, 2013;Tanyel et al, 2013). In contrast, allele-D32 is rarely seen in Asian and African countries (Table 4).…”
Section: Discussioncontrasting
confidence: 60%
“…In Portugal, one of the countries that has most significantly influenced the genetic background of the Brazilian population, a frequency of 8% was reported for the general population, which is at the limit of statistical significance when compared with the frequency observed in this study (P = 0.05) (Carvalho et al, 2014). In Middle Eastern countries, variation in the allele-D32 frequency was more apparent, ranging from 0.6-14%, with the highest frequencies found in Turkey (9.1%) and Israel (14.3 %) (P < 0.05) (Martinson et al, 2000;Khabour et al, 2013;Tanyel et al, 2013). In contrast, allele-D32 is rarely seen in Asian and African countries (Table 4).…”
Section: Discussioncontrasting
confidence: 60%
“…The frequencies of the CCR2-64I allele in African populations have been higher than what has been observed in Caucasians (7%–10%), while Asian populations show a wider range from 1%–30% 22. A study on subjects selected from different regions of Jordan showed that this allele is common among Jordanians, with a prevalence of 17.5% 8. The CCR2-64I mutation appears to be common in all ethnic groups,10 and the observation is in accordance with the theory that it is an ancient one 23.…”
Section: Discussionmentioning
confidence: 90%
“…The SDF1‐3′A allele frequency ranges widely across different global populations ranging from 1% to 43%. SDF1‐3′A allele frequency has been reported to be high in Asians and Arabs (Voevodin et al ., ; Ikegawa et al ., ; Ramana et al ., ; Wang et al ., ; Verma et al ., ; Salem et al ., ; Amara et al ., ; Khabour et al ., ) in contrast to very low SDF1‐3′A allele frequency in Africans (Magierowska et al ., ; Petersen et al ., ), Table S1.…”
Section: Resultsmentioning
confidence: 99%